Structure Study of Magnetic Thin Films for Voltage Controlled Spintronics by Scanning Transmission Electron Microscopy Experiment and Density Functional Theory Calculations - Sun, Congli (University of Wisconsin-Madison, 2017)
We have studied magnetic thin films for voltage controlled magnetic tunnel junctions (MTJs) by advanced scanning transmission electron microscopy (STEM) and density functional theory (DFT) simulations. MTJs are the prototypical spintronic device and manipulation of magnetism by electrical means is among the most promising approaches to novel voltage-controlled spin electronics. Compared with the present metal-oxide-semiconductor devices, voltage-controlled spintronics have great advantage of reducing power consumption and enhancing processing speed. The voltage controlled magnetic effect can be achieved across many different materials systems, such as voltage-induced magnetization phase transitions, electric-field control of coercivity and electric control of magnetic anisotropy, all of which depend on high-quality thin films with minimum crystallographic defects. Cr2O3 is antiferromagnetic in bulk but ferromagnetic on the (0001) surface. Bulk Cr2O3 has two degenerate antiferromagnetic states with opposite (0001) surface spin polarization. As Cr2O3 is also magnetoelectric, the degenerate antiferromagnetic states can be lifted by manipulating the free-energy gain ΔF=aEH. Therefore, the surface ferromagnetism can be controlled by changing the sign of applied electric field. Compared with bulk Cr2O3, high leakage current, low breakdown voltage, low magnetic ordering temperature and high EH products to observe magnetoelectric effect are commonly observed in Cr2O3 thin films. Hence, it is essential to understand the film microstructure and its relationship to the substrate conditions. We have observed vertical grain boundaries in Cr2O3/Al2O3 systems that are related with a 60 in-plane rotation by diffraction contrast TEM image. STEM as a function of scattering angle points out a simultaneous 1⁄3[101 ̅0] basal plane shift. Local boundary electron energy loss spectroscopy (EELS) shows a pre-peak on the O K-edge arising from unoccupied O 2p states, indicating a reduced bandgap along the boundary that provides potential breakdown paths in Cr2O3 thin films. B doping of Cr2O3 is known to increase the Néel temperature. B was found to form either BCr4 tetrahedra or BO3 triangles in the Cr2O3 lattice, with σ^* and π^* bonds exhibiting different energy loss features. Modeling the experimental spectra as a linear combination of simulated B K edges reproduces the experimental π^* / σ^* ratios for 12 to 43 % of the B in the sample occupying BCr4 sites. Simulated BCr4 fraction / total B as a function of oxygen partial pressures supports the EELS results and indicates further increase of Néel temperature can be achieved by optimizing oxygen partial pressures. We also investigated the GdOx/Co/Pt systems, in which the voltage effect comes from the oxygen migration through the Co layer to the Co/Pt interface. Hybridization between O 2p and Co 3d states modifies the energy of Co 3d orbitals, introducing crystal field effects that favor 3d orbital anisotropy. STEM EELS were performed to study spatial oxidization heterogeneity by voltage-induced oxygen migration in 4 nm Co films that results in tunable perpendicular. Depth profiles of oxygen migration under applied voltage histories, as well as the structural origin of perpendicular magnetic anisotropy (PMA) is revealed. Particularly, an intermediate PMA state was achieved by a combination of negative and positive voltages, with residual CoOx at Pt/Co interface and abrupt oxygen concentration boundary in the Co layer.
Keywords: electron microscopy, spintronics, magnetic tunnel junctions, Cr2O3